Communicating ethical sourcing - Anderson, Ingrid; Bæcklund, Johanna (2015)
Palm oil has been used in processed food commodities since the 19th century. An increasing demand for regulating and ensuring a more sustainable palm oil production has resulted in various initiatives. However, these initiatives have received critique due to lack of compliance and insufficient revisions of palm oil plantations. The initiatives for creating an ethical, social and environmentally sustainable production are not sufficient for the Swedish industrial users of palm oil. As a result, stakeholders such as Swedish food processing companies, commit to ethical sourcing codes of conduct that go beyond the international palm oil initiatives. Since this industrial initiative does not have a third party audit procedure, transparency is a key objective to create grounds for legitimacy, which is also in part determined by how the initiative is communicated. The aim of this thesis is to explain communication strategies where corporations account for ethical sourcing efforts. The thesis investigates how companies operating in the Swedish food processing industry communicate their use of palm oil. Communicational strategies were analysed through the company’s communication of corporate social responsibility, where the understanding of risk-management, needs for legitimacy and use of codes of conduct serve as a contextual framework. In this study, a qualitative research with a case study approach was used. The case study involved three case companies and one trade association. Case company representatives were interviewed by using semi-structured interviews. The results of the interviews were further discussed by interviewing a representative from the Swedish Food Federation who initiated a sustainable palm oil initiative in the Swedish palm oil industry 2015. Findings in this study show the importance for the case companies to communicate their account for ethical sourcing efforts. The case companies that implemented a proactive corporate social responsibility strategy, which focuses on transparency, creating grounds for legitimacy and communicating ethical sourcing efforts. Additional findings of this study indicate that the case companies’ accountings for ethical sourcing efforts were affected by views of the external stakeholders. A critical review of a company may still result in positive attitudes towards a company, if the company manages to carry out communication in a transparent and trustworthy manor. In other words, negative publicity may be converted to positive action in a proactive communication strategy. Through communication, for instance with codes of conduct, a company show how corporate responsibility is enacted. Furthermore, the findings in this study show that through pressure from authorities and other external stakeholders, the case companies became motivated to communicate their ethical sourcing. The palm oil initiative is seen as an industrial networking initiative, where legitimacy and values are created through corporate codes of conduct.